Integration of Character Education into the Management of Independent Curriculum-Based Learning in Elementary Schools - Resnita, Resnita (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2025)
Integration of character education through the management of Independent Curriculum-based learning in schools is an important learning pattern to be implemented, especially in Elementary Schools as the initial phase of critical individual development. This research was conducted at SD Negeri 2 Selat Penuguan. The method used is a qualitative method. Data collection tools use interview methods, documentation, observation and literature review. Data analysis uses descriptive qualitative analysis. The results of the study state that the integration of character education into the management of Independent Curriculum-based learning is carried out with learning planning designed through ATP and character education-based teaching modules. The implementation of learning focuses on the implementation of holistic learning, namely increasing achievement in line with student character development. Learning assessment uses a holistic approach that emphasizes the evaluation of academic achievement by viewing individual differences as part of the characteristics of each student.